1979
DOI: 10.1136/pgmj.55.643.343
|View full text |Cite
|
Sign up to set email alerts
|

Liver and gastrointestinal function in pregnancy

Abstract: Summary Difficulties arise in the interpretation of liver tests in the pregnant subject, since some values increase (alkaline phosphatase) whilst others remain unchanged (transaminases) or fall during pregnancy. The diagnosis and management of some causes of jaundice in pregnancy, such as viral hepatitis, gall stones, benign intrahepatic cholestasis and acute fatty liver of pregnancy are discussed. Little is known about the commonest symptoms of pregnancy (nausea, vomiting and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…(2) including 85 patients with PIH, AST, ALT were elevated in 54% of patients with pre-eclampsia, whereas in cases of gestational hypertension they were raised only in 14% of cases.…”
Section: Hepatic Transaminases-ast and Altmentioning
confidence: 85%
“…(2) including 85 patients with PIH, AST, ALT were elevated in 54% of patients with pre-eclampsia, whereas in cases of gestational hypertension they were raised only in 14% of cases.…”
Section: Hepatic Transaminases-ast and Altmentioning
confidence: 85%
“…Abnormal liver function tests occur in 20% to 30% of pregnancies complicated by pre-eclampsia and are associated with poor maternal and fetal outcomes. 11,12,14 Various authors have reported alterations in liver enzymes in preeclampsia patients. [15][16][17] Age and parity (Graph 1 and 2): Spectrum of pre-eclampsia is more common in extremes, of reproductive age groups.…”
Section: Discussionmentioning
confidence: 99%